PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENYELUNDUPAN SATWA JENIS TRENGGILING YANG DILINDUNGI DI WILAYAH HUKUM KEPOLISIAN DAERAH RIAU - Fitri Febriyati; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia is a country that has the largest biological natural resources and ecosystems consisting of vegetable natural resources and animal natural resources. The elements of biological natural resources and their ecosystems are basically interdependent with each other so that the use of one element will affect other elements of natural resources, damage and extinction of one of the elements that will result in disruption of the ecosystem. The extinction of several species of protected animals so far many have been damaged or deliberately damaged by various acts of a group of people who are not responsible. The extinction of these animals is caused by humans who carry out illegal animal trade by smuggling protected animals into neighboring countries. The trade in endangered species is still carried out illegally and is still difficult to eradicate because the trade in protected animals is very popular.The purpose of this thesis is; First, to find out the factors causing the occurrence of criminal acts of smuggling of pangolin species that are protected in the jurisdiction of the Riau Regional Police; Second, to find out law enforcement against the perpetrators of the crime of smuggling pangolin species protected in the jurisdiction of the Riau Regional Police.This type of legal research used by the writer is a type of sociological juridical research, because in this study the writer directly conducts research at the location or place under study.From the results of the study, there are two main things that can be concluded. First, the factors that cause the smuggling of protected animals, namely, economic factors, law enforcement factors, environmental factors that are not good, and factors of lack of social control from family and community environment, and not yet maximum social control from family and community environment, not yet maximum control from the government in protecting these protected animals. And there are also several factors that cause the crime of smuggling these animals, namely, community factors, high selling value factors, conflict factors between humans and animals, hobby factors, and factors less than optimal processes for imposing criminal sanctions. Second, law enforcement against traffickers of protected species of pangolins based on Law Number 5 of 1990 concerning Conservation of Biological Resources and Their Ecosystems in the Riau Regional Police jurisdiction has been running properly but there are only a few law enforcement officers involved in it . This must be realized by law enforcers and individuals that the smuggling of protected animals has a great influence on the ecosystem.Keywords: Law Enforcement, Crime, Anteater Smuggling